Attention to advertising and memory for brands under alcohol intoxication - Orquin, Jacob L. (Frontiers Media S.A., 2014)
In an attempt to discover new possibilities for advertising in uncluttered environments marketers have recently begun using ambient advertising in, for instance, bars and pubs. However, advertising in such licensed premises have to deal with the fact that many consumers are under the influence of alcohol while viewing the ad. This paper examines the effect of alcohol intoxication on attention to and memory for advertisements in two experiments. Study 1 used a forced exposure manipulation and revealed increased attention to logos under alcohol intoxication consistent with the psychopharmacological prediction that alcohol intoxication narrows attention to the more salient features in the visual environment. Study 2 used a voluntary exposure manipulation in which ads were embedded in a magazine. The experiment revealed that alcohol intoxication reduces voluntary attention to ads and leads to a significant reduction in memory for the viewed ads. In popular terms consuming one or two beers reduces brand recall from 40 to 36% while being heavily intoxicated further reduces brand recall to 17%.